2022
DOI: 10.1016/j.colegn.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Areas of nursing competence in acute wound care: A focus group study

Abstract: Background: Wound care is an essential part of registered nurses' work. However, previous studies have indicated that registered nurses have limited competence in this area. Studies have also highlighted the lack of consistent and standardised areas of competence for registered nurses providing wound care.Aim: To identify general areas of competence for registered nurses providing acute wound care during their transition from student to healthcare professional.Methods: Focus group interviews were used to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…58 Enabler: understanding of wound healing phases, differentiating inflammatory phase from the signs of an infection. 59 Utilising wound care guidelines and dressing algorithms to assist decision making. 37 Knowledge (including knowledge of condition/scientific rationale)…”
Section: Knowledgementioning
confidence: 99%
“…58 Enabler: understanding of wound healing phases, differentiating inflammatory phase from the signs of an infection. 59 Utilising wound care guidelines and dressing algorithms to assist decision making. 37 Knowledge (including knowledge of condition/scientific rationale)…”
Section: Knowledgementioning
confidence: 99%
“…[1][2][3][4] Research indicates that physicians and nurses do not receive adequate wound education, perpetuating wound mismanagement. [5][6][7][8][9][10][11][12][13] Wounds that are not managed appropriately may result in delayed healing, complications, decreased quality of life, and increased healthcare costs. 3,4,14…”
Section: Introductionmentioning
confidence: 99%
“…The chronic wound has been assigned as a major public health problem associated with very high economic costs, representing 2–4% of the total health system costs in the West ( Magin et al, 2016 ; Rodrigues et al, 2019 ; Azevedo et al, 2020 ). Maaz Arif et al( 2021 ) and Kielo-Viljamaa et al (2021 ) reported that approximately 1–2% of the population in the developed countries suffers from chronic wound. As has been explained by other authors, the hindered closure of nonhealing (chronic) wounds (namely pressure ulcer, static venous ulcer, and diabetic wounds, etc.)…”
Section: Introductionmentioning
confidence: 99%